The Existence of Subak in The Legal Politics of Development Program in Bali - Sarna, Kadek (Kertha Patrika; Vol 43 No 3 (2021)DO - 10.24843/KP.2021.v43.i03.p02, 2021)
This study aimed to analyze the legal policies of Bali regional development planning in providing protection for the existence of Subak sustainability in development. This study employed a normative legal research method with a statutory approach, and analytical conceptual approach. The results indicated that the existence of Subak has been recognized as a model of management irrigation in Bali that has been inherited by ancestors, which is protected by the 1945 Constitution. However, the direction of regional development planning within the framework of autonomy, places the agricultural sector as the preferred government affair of the regional government authority. Hence, it causes the agricultural sector does not become the leading sector in development planning, and beside the priority of the agricultural budget from the portion of planning and regional economic development, which is still below 2% (two percent). There are also a lack and difficulties in synergizing regional development in agriculture with efforts to protect Subaks across districts/cities in the province of Bali.